Safety Profiles of Tripterygium wilfordii Hook F: A Systematic Review and Meta-Analysis - Zhang, Chi; Sun, Ping-Ping; Guo, Hong-Tao; Liu, Yan; Li, Jian; He, Xiao-Juan; Lu, Ai-Ping (Frontiers in Pharmacology, 2016)
Objective: Tripterygium wilfordii Hook F (TwHF) is a widely used and effective treatment for inflammatory diseases. There have been concerns about its toxicity but no adequate synthesis of the evidence for adverse events (AEs). We aimed to undertake a clinically informative, systematic safety profile of TwHF. Methods: We undertook a systematic review and meta-analysis of experimental studies and observational studies. We searched electronic databases and conference abstracts. Safety outcomes were rates of common AEs. Results: We screened 4,137 abstracts for eligibility and included 594 studies in the analysis. The overall incidence of AEs was 26.7% (95% CI 24.8%, 28.8%) in 23,256 TwHF users. The estimates did vary markedly when stratified by specific study types. The incidence of gastrointestinal symptoms, adverse reproductive outcomes, adverse skin reactions, hematologic events and cardiovascular events were 13.3% (95%CI 11.9%, 14.9%), 11.7% (95% CI 10.3%, 13.3%), 7.8% (95%CI 6.3%-9.5%), 6.5% (95%CI 5.7%-7.4%) and 4.9% (95%CI 1.6%, 14.3%), respectively. The prevalence of irregular menstruation (IM) was increased in patients taking TwHF compared with those given control (odds ratio [OR] 4.65, 95% CI 3.08 to 7.03). TwHF use has lower risk of weight gain (OR 0.12 [95%CI 0.04 to 0.39]) and hair loss (OR 0.37 [95% CI 0.18 to 0.78]). Furthermore, long-term aspirin use (> 6 months) has a higher AEs incidence (31.0% [95% CI 24.5%-38.5%]). Conclusion: Our findings suggest that more than one in four patients who were taking TwHF had experienced AEs. A clear need exists for improved understanding of contributing risk factors, as well as of prevention and management strategies to improve patients' tolerance for TwHF.